Supporting the implementation of drinking water management systems in New South Wales, Australia - Tran T. Huynh; Leslie Jarvis; Wendy Henderson; Zenah Bradford-Hartke; Sandy Leask; Katherine Gajo; Joshua Tickell; Katrina Wall; Paul Byleveld (IWA Publishing, 2023)
Since 2010, New South Wales (NSW) Health has assisted local water utilities to develop and implement risk-based drinking water management systems based on the Australian Drinking Water Guidelines Framework for Management of Drinking Water Quality. This support has benefited regional communities, and especially smaller utilities, by helping to identify and control risks. NSW Health's support projects have resulted in statistically significant improvements across many elements of drinking water management system implementation. Through this program of support, NSW Health has identified possible infrastructure and operational needs and assessed implementation of drinking water management systems. In parallel, NSW Health has worked to assess the risk from Cryptosporidium in drinking water supplies and to develop a formal audit program. Findings from the NSW Health support program informed the development of two NSW Government programs and the commitment of more than $1 billion to help local water utilities address public health and other critical needs. The introduction of risk-based drinking water management systems has driven incremental improvement in drinking water quality management across the state of NSW. HIGHLIGHTS NSW Health supports regional water utilities implement risk-based drinking water management systems.; Standardised questionnaires are used to demonstrate statistically significant improvements in implementation.; Outputs coded into a database and assigned risk ratings to prioritise further support.; Priorities for support inform investment in infrastructure.; Incremental improvements seen in water quality management.;